La educación en el Protectorado español en Marruecos a través de tres revistas de la Liga Africanista Española (1913-1931) - Rubio Mayoral, Juan Luis; Sanchidrián-Blanco, María del Carmen (My University, 2017)
Colonialism and postcolonialism are important stages in the history of many European countries such as Great Britain, France, Holland, Portugal or Spain. However, rarely are the colonies taken into account in the history of education of these countries. In the case of Spain, it has scarcely been explored throughout most of the Century XX. The establishment of the Protectorate in the north of Morocco in 1912 meant the need to put in place measures to control the territory and the population. From early on, education was considered as an colonisation agent and several models of education appeared: colonial school, traditional school and nationalist school. Each one had a different target audience and different aims. The Digital Periodicals Library of the National Library offers three journals on the Spanish Protectorate in Morocco. They present a continuity between 1913 and 1931. The first is África Española. Revista de Colonización (1913-1917). This one was followed by Boletín de la Liga Africanista Española (1917-1923) and later by Revista hispano africana (1923-1931). Our main goal is to analyze the contents of these journals of the Spanish Africanist League on education, grouping them around descriptors such as educational levels, teachers and debates on education, as well as the impact of the Spanish culture on the Protectorate throughout the educational institutions.
The education under the Spanish Moroccan Protectorate throughout three magazines of the Spanish Africanist League (1913-1931)
Keywords: Educación - Marruecos - Historia - 1912-1956 (Protectorado español); Colonialism; Spanish Moroccan Protectorate; Education in Africa; 20th century